2012
DOI: 10.4236/act.2012.12003
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Method for Cardiac Output Estimation by CT Coronary Angiography

Abstract: Background: Cardiac output can be estimated during retrospectively gated CT coronary angiography by anatomically determining left ventricular volumes; prospective triggering to minimize radiation precludes this methodology. We propose an alternative method for cardiac output estimation based on preclinical models suggesting that cardiac output may be inversely related to contrast washout from the aortic root during timing bolus scanning, as measured by peak aortic root contrast attenuation. Methods: 34 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This is, to our knowledge, the first report on estimated test-bolus employing a mathematical compartment model validated against findings of CO from MRI. Our findings are in accordance with findings of a moderately high correlation between estimated CO by CT validated with echocardiography ( 20 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is, to our knowledge, the first report on estimated test-bolus employing a mathematical compartment model validated against findings of CO from MRI. Our findings are in accordance with findings of a moderately high correlation between estimated CO by CT validated with echocardiography ( 20 ).…”
Section: Discussionsupporting
confidence: 92%
“…Ultrasonic contrast agents have been used to improve image quality for echocardiography, [ 10 ] but a potential role in assessment of PVR and CO has not yet been defined. Investigators using other imaging modalities have suggested using transit times to assess these measures [ 11 13 ]. In this prospective pilot study, we tested the hypothesis that transit time assessment during contrast-enhanced echocardiography could accurately estimate both PVR and CO compared to the gold-standard of RHC in patients without evidence of structural right heart disease.…”
Section: Introductionmentioning
confidence: 99%